Implementasi Bisnis Model Canvas pada Produk Indomilk UHT Jeju Chocolate - Yura, Annisya; Idris, Iswandi; Maulidina; Silalahi, Flora; Nirina (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2022)
This study aims to analyze the business model of Indomilk UHT Jeju Chocolate products using the Business Model Canvas framework. This analysis was conducted to identify key elements that support the success of the product and formulate strategies that can be implemented to improve business performance. The research approach is descriptive qualitative with data collection methods through interviews, surveys, and document analysis. The collected data were analyzed using the Business Model Canvas framework and SWOT analysis. The results showed that product innovation and effective marketing strategies are the main success factors for Indomilk UHT Jeju Chocolate. The unique value of the product, such as Jeju chocolate flavor, is able to attract consumer attention and increase competitiveness in the market. However, this study has limitations in survey and interview data that may not fully represent the consumer population as a whole. Future research is recommended to expand the sample and use quantitative methods to obtain a more in-depth analysis. This research provides academic contributions in the form of literature on Business Model Canvas as well as practical benefits for Indomilk in formulating more effective business strategies, especially in product innovation and marketing strategies.